MODELAGEM MATEMÁTICA: UMA PROPOSTA PARA O ENSINO DE ESTATÍSTICA - Batista, Paulo Roberto (2013)
Statistics is considered a science that provides methods for the collection, organization, description, analysis and interpretation of data, in order to draw conclusions about the object of study and, therefore, assist in decision making. It plays a fundamental role as a basis for practical resolutions of problems in various areas of knowledge, in this way, directly or indirectly, it is present in the daily lives of all citizens without distinction. Thus, increasingly, the statistic should contribute to the citizenship of our students and the entire society which critically and consciously need to make accurate and appropriate decisions for every problem they face. In this context, mathematics teachers have the important task of creating a connection between the statistical concepts and realities of students, using existing technologies and methodologies that lead to a consistent better learning. In view of the above, this study has the objective to investigate what the consequences of Mathematical Modeling environment can provide to the teaching and learning of statistics in high school. Therefore, the research objectives are characterized as: recommend the study of Statistics through Mathematical Modeling Methodology juncture in high school and so research and discuss the results that this learning environment can provide to the teaching and learning of statistics; defend and give value to the development of the student, with regard to the critical aspects, awareness of the seriousness of their participation in society and the competence to integrate academic content with their day-to-day life. In order to accomplish all of that, we try to base the research in relation to Education Statistics, as well as present the design of mathematical modeling through literature review and practical application of a problem situation that summarizes the process of statistical investigation.